2021
DOI: 10.1002/arp.1835
|View full text |Cite
|
Sign up to set email alerts
|

Prehistoric chamber tombs or geological pitfall? A multimethod case study from Ancient Aigeira with a focus on seismic full‐waveform inversion

Abstract: We show an extensive multimethod geophysical study of focusing on some enigmatic subsurface structures found at Ancient Aigeira (N Peloponnes, Greece) that could be interpreted either as prehistoric chamber tombs or complex weathering patterns of the local marl–conglomerate rock sequences. It turns out that the nonseismic methods do not allow to distinguish between an archaeological and a geological origin of the observed patterns with certainty. In contrast, we demonstrate how shear‐wave seismics and full‐wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 37 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…In terms of wave theory, the maximum achievable resolution corresponds to the quarter‐wavelength criterion well known from classical reflection seismics. However, previous studies have shown the high‐resolution capabilities of the applied FWI algorithm (e.g., Dokter et al, 2017; Köhn et al, 2019; Rusch et al, 2022). All studies show that structures with dimensions smaller than 1.0 m by 1.0 m could be reliably resolved, making the FWI a promising tool for the investigation of dikes.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In terms of wave theory, the maximum achievable resolution corresponds to the quarter‐wavelength criterion well known from classical reflection seismics. However, previous studies have shown the high‐resolution capabilities of the applied FWI algorithm (e.g., Dokter et al, 2017; Köhn et al, 2019; Rusch et al, 2022). All studies show that structures with dimensions smaller than 1.0 m by 1.0 m could be reliably resolved, making the FWI a promising tool for the investigation of dikes.…”
Section: Discussionmentioning
confidence: 98%
“…Using synthetic resolution tests, Dokter et al (2017) investigated the spatial resolution for the same FWI algorithm. Rusch et al, 2022 applied the FWI as part of a multimethod geophysical study to distinguish between interpretation hypothesizes for observed structures obtained by nonseismic methods achieving a resolution on the decimetre scale and Mecking et al (2021) use FWI for cavity detection inside a high monumental antique grave mount. The potential of the FWI to resolve the internal structures of a sea dike was investigated in a study by Köhn et al (2018), where a high correlation between the SH‐wave velocity structure and the lithology known from corings was observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations